Inferring ‘weak spots’ in phylogenetic trees: application to mosasauroid nomenclature - Madzia,Daniel; Cau,Andrea (PeerJ, 2017)
Mosasauroid squamates represented the apex predators within the Late Cretaceous marine and occasionally also freshwater ecosystems. Proper understanding of the origin of their ecological adaptations or paleobiogeographic dispersals requires adequate knowledge of their phylogeny. The studies assessing the position of mosasauroids on the squamate evolutionary tree and their origins have long given conflicting results. The phylogenetic relationships within Mosasauroidea, however, have experienced only little changes throughout the last decades. Considering the substantial improvements in the development of phylogenetic methodology that have undergone in recent years, resulting, among others, in numerous alterations in the phylogenetic hypotheses of other fossil amniotes, we test the robustness in our understanding of mosasauroid beginnings and their evolutionary history. We re-examined a data set that results from modifications assembled in the course of the last 20 years and performed multiple parsimony analyses and Bayesian tip-dating analysis. Following the inferred topologies and the ‘weak spots’ in the phylogeny of mosasauroids, we revise the nomenclature of the ‘traditionally’ recognized mosasauroid clades, to acknowledge the overall weakness among branches and the alternative topologies suggested previously, and discuss several factors that might have an impact on the differing phylogenetic hypotheses and their statistical support.
Keywords: Mosasauroidea; Phylogeny; Parsimony analysis; Bayesian inference; Phylogenetic nomenclature; Fossilized birth-death model; Late Cretaceous